Deletion of miR-126a Promotes Hepatic Aging and Inflammation in a Mouse Model of Cholestasis - Yan, Yi (Mol Ther Nucleic Acids, 2019)
MicroRNAs (miRNAs) act as regulators of aging at the tissue or organism level or as regulators of cellular senescence. Targeted deletion of miR-126 in mice causes partial embryonic lethality, but its biological function in the liver is still largely unknown. Here, we deleted miR-126a, using the CRISPR/Cas9 system in vitro and in vivo. miR-126a was reduced in the aging livers, and disruption of miR-126a in bone mesenchymal stem cells (BMSCs) induced age-associated telomere shortening, DNA damage responses, and proinflammatory cytokines. Moreover, disruption of miR-126a in mice caused hepatocyte senescence, inflammation, and metabolism deficiency. In addition, disruption of miR-126a via BMSC transplantation aggravated the severity of liver defects induced by cholestasis compared with that in the functional miR-126a BMSC group. Mechanistically, we identified versican (VCAN) as a novel direct miR-126a-5p target that induces telomere shortening, BMSC senescence, and nuclear factor κB (NF-κB) pathway activation. This study identified aging-related reduced expression of miR-126a and promotion of its target VCAN as a key mechanism in the regulation of hepatic metabolic function during aging and hepatic damage by inducing NF-κB pathway activation, DNA repair function disorder, and telomere attrition. The findings indicate that miR-126a may be a drug target for the treatment of hepatic failure.